2000
DOI: 10.1097/00004032-200012000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Effective Thresholds for Induction of Skeletal Malignancies by Radionuclides

Abstract: Our analysis of data from the beagle project completed at the University of Utah has provided some comparisons that appear to be useful in testing the model proposed by Raabe of effective thresholds for induction of skeletal malignancy by bone-seeking radionuclides in beagles. Raabe's model predicted that cumulative skeletal doses of less than about 0.9 to 1.4 Gy from alpha emitters or 28 to 70 Gy from beta emitters deposited in the skeleton require a long enough time for bone cancer expression that the dog's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The resulting inferred estimate was 1.5 bone sarcomas per million persons who had ingested an environmentally relevant dose of 0.18 Bq U d Ϫ1 (Mays et al 1985). Recent studies have shown that there may be an effective threshold for the induction of bone sarcomas by alpha-emitting radionuclides, indicating that virtually no cancer would be expected from environmental concentrations of uranium (Rowland 1995;Lloyd et al 2000).…”
Section: Toxicity Of Uraniummentioning
confidence: 99%
“…The resulting inferred estimate was 1.5 bone sarcomas per million persons who had ingested an environmentally relevant dose of 0.18 Bq U d Ϫ1 (Mays et al 1985). Recent studies have shown that there may be an effective threshold for the induction of bone sarcomas by alpha-emitting radionuclides, indicating that virtually no cancer would be expected from environmental concentrations of uranium (Rowland 1995;Lloyd et al 2000).…”
Section: Toxicity Of Uraniummentioning
confidence: 99%
“…Late effects, such as carcinogenesis has been observed following administration of R-particle emitters. [178][179][180][181][182][183][184] For therapy of nonterminal patients, the probability for induction of such late damage needs to be addressed. 185,186 More accurate knowledge of late damage induction probabilities may come from microbeams [187][188][189] or the retrospective absolute R-particle hit determination method.…”
Section: Normal Tissue Damagementioning
confidence: 99%
“…These findings hold promise for cancer therapeutic applications of 212/213 Bi, though further studies are warranted. Late effects, such as carcinogenesis has been observed following administration of α-particle emitters. For therapy of nonterminal patients, the probability for induction of such late damage needs to be addressed. , More accurate knowledge of late damage induction probabilities may come from microbeams or the retrospective absolute α-particle hit determination method …”
Section: Normal Tissue Damagementioning
confidence: 99%
“…Stron -tium-90 (max i mum ben ergy 0.5 MeV) has a short-lived daugh ter, 90 Y (T 1/2 = 64 h), which is a very poor g-emit ter as well, but a pow er ful b --emit ter with a max i mum b --en ergy of 2.3 MeV. Bone-seek ing radiostrontium ad versely af fects the bone and the bone mar row and may cause leu ke mia [9] or skel e tal ma lignan cies [10], thus giv ing rise to the need of its mon i toring (es pe cially in food) af ter nu clear ac ci dents [11][12][13][14]. Fol low ing the Fukushima ac ci dent, only few stud ies were con ducted with re spect to the mon i tor ing of 90 Sr [11,15].…”
Section: Introductionmentioning
confidence: 99%